Context-aware link scheduling in static wireless networks with successive interference cancellation - Shao-he LV; Xiao-dong WANG; Xing-ming ZHOU (Tongxin xuebao)
Greedy link scheduling based on the physical model was studied in a static wireless network with SIC.In general,there were two major stages in a greedy scheduling scheme,link selection,i.e.,to decide which link was scheduled next,and time slot selection,i.e.,to decide which slot was allocated to a given link.Most available schemes took a first-fit policy in the second stage and became less efficient when SIC was available.For the time slot selection stage,tolerance margin was defined to measure the saturation of a link set and two heuristic policies were presented:one was to schedule a link to a slot such that the resulting set of links had a maximum tolerance margin; the other was to choose a slot such that the decrease of tolerance margin was minimum.Simulation results show that the performance of the proposed schemes is much better than the first-fit policy.